Response of Drainage Pattern and Basin Evolution to Tectonic and Climatic Changes Along the Dinarides-Hellenides Orogen - Gemignani, L.; Mittelbach, B. V.; Simon, D.; Rohrmann, A.; Grund, M. U.; Bernhardt, A.; Hippe, K.; Giese, J.; Handy, M. R. (Frontiers in Earth Science, 2022)
The junction of the Dinaric and Hellenic mountain belts bordering the Adriatic Sea (central Mediterranean) is the site of a trans-orogenic normal fault system (the Shkoder-Peja Normal Fault or SPNF) that has accommodated oroclinal bending, as well as focused basin formation and drainage of the Drin River catchment. We provide new insight on the temporal and spatial scales on which lithospheric deformation (slab retreat, orogenic bending) has interacted with surface and climatic erosion (glacial and fluvial) to induce a drastic reorganisation of river drainage since the Last Glacial Maximum (LGM). Analysis of fluvial morphology of the Drin River system reveals higher values of river slope indices (ksn) and χ (Chi) between the normal faults of the SPNF and the Drin drainage divide. The drainage divide is predicted to be migrating away from the SPNF, except at the NE end of the SPNF system. Two basins analysed in the hangingwall of the SPNF, the Western Kosovo Basin (WKB) and Tropoja Basin (TB), contain flat-lying late Pliocene-to-Holocene sedimentary rocks deposited well after the main fault activity and immediately after the LGM. These sediments document a transition from lacustrine to fluvial conditions in early Pleistocene time that reflects a sudden change from internal to external drainage of paleo-lakes. In the Tropoja Basin, these late- to post-LGM layers were successively incised to form three generations of river terraces, interpreted to reflect episodic downstream incision during major reorganisation of the paleo-Drin River drainage system. New 36Cl-cosmogenic-nuclide depth-profile ages of the two youngest of these terraces (~12 and ~8 ka) correlate with periods of wetter climate and increased sediment transport to the TB in post-LGM time. The terraces yield an incision rate of ~13 mm/yr, an order-of-magnitude greater than those previously reported in central and southern Albania. Taken together, it appears that glacial/interglacial climatic variability, hinterland erosion and base-level changes regulated basin filling and excavation cycles at a time when the rivers draining the WKB and TB became part of the regional river network emptying into the Adriatic Sea.